Association of youth health care transition readiness to role overload among parents of children with chronic illness. (23rd May 2019) - Hart, Laura C.; van Tilburg, Miranda A.L.; Campbell, Robert; Faldowski, Richard A.; Nazareth, Meaghan; Ndugga, Maggwa; Coltrane, Chad; de Ferris, Maria Diaz‐Gonzalez
Abstract: Background: A parent's level of role overload, a situation in which the demands of an individual's roles are beyond their capacity to perform adequately, has been associated with poor outcomes in adolescents. It is unknown if role overload in parents is associated with less health care transition (HCT) readiness in their children with chronic conditions. We sought to assess this relationship. Methods: Youth with chronic conditions attending a therapeutic camp and their parents completed online consents/assents and de‐identified surveys. Parents reported on parental role overload using the Reilly Role Overload Scale and a proxy assessment of the youth's HCT readiness using the STARx —Parent Questionnaire. Youth self‐reported on their HCT readiness using the STARx Questionnaire. Linear regression measured the relationship between parent role overload and HCT readiness, controlling for youth's age, sex, and degree of youth's educational support. Results: One hundred fifty‐two parents and 50 youth completed the measures. Greater parental role overload was associated with less overall HCT readiness on the parent proxy measure ( β = −.12, P ≤ .008) and a lower level in the self‐management domain on the parent proxy measure ( β = −.20, P ≤ .001). We found no associations between parent role overload and youth self‐report of HCT readiness. Conclusion: Parent's level of role overload had no association with youth's self‐report of HCT readiness but was negatively associated with parent proxy report of their youth's HCT readiness, suggesting that parents with high levels of role overload may perceive their youth as less ready to transition to adult‐focused care.